Cognitive function of cancer patient before and after chemotherapy. Directions for additional medical treatment and psychological aid in recovering mental abilities. Analysis of two case studies – students: woman and man - Pietrzyk, Agnieszka (Psychoonkologia, 2010)
Aim of the study : Analysis of subtle cognitive impairment of two students cancer survivors. Material and methods : A woman 21-years-old with ovary cancer and a man 21-year-old too with testis cancer took part in one year’s neuropsychological training of their cognitive functions. A man accepted the additional treatment of procognitive drugs but a woman did not. Consistent with references of International Cognition and Cancer Task the battery of cognitive tests of WAIS-R were used. Results : One year’s neuropsychological therapy improved the cognitive functions of both students. Nevertheless they reported deline in attention, concentration and cognitive energy. The woman also complained the difficulties in planning, anticipation and organization of her cognitive activities. Conclusions : The results received in the present analysis demonstrate a new area for psychooncological studies and for additional treatment of young cancer survivors suffering cognitive impairment after chemotherapy.